Salvage Therapy for Refractory Aids-Related Primary Central Nervous System Lymphoma - Hugo Ferro; Eduardo Parino (Case Reports in Oncological Medicine)
A 27-year-old male patient presented with speech disorders and multiple brain masses on MRI evaluation. He tested positive for HIV. A sterotactic biopsy diagnosed primary central nervous system lymphoma (diffuse large B-cell lymphoma). After two cycles of high-dose metotrexate (HD-MTX-)-based chemotherapy, the tumor progressed. He underwent whole brain radiotherapy achieving complete response. Six cycles of consolidating immunochemotherapy with rituximab-temozolomide were administered after radiation. Forty-three months after remission, he has not recurred and his neurological status is optimal. Younger HIV patients with refractory PCNSL and preserved immune function can face salvage therapy successfully achieving long term remissions with no remarkable neurotoxicity.